MODERN INNOVATIVE BUSINESS STRATEGIES IN THE FOOD INDUSTRY SYSTEM OF UKRAINE - SEMBAY, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the peculiarities of the development of innovative business in the system of the food industry of Ukraine, aimed at increasing the efficiency of production and ensuring the operation of enterprises. The author of the article examines modern innovative business strategies in Ukraine, attests to their multifunctionality and the importance of taking into account current aspects of the development of the modern economy. He also analyzes various options for innovative development of the food industry, models, technologies and scenarios aimed at successful innovative business and determines new approaches and influencing factors regarding the application of modern strategies of innovative business, a set of relevant measures capable of ensuring real changes in the food industry.The article emphasizes that against the background of the decline and significant lag behind the food industry of Ukraine from the progressive countries of the world, it has all the opportunities to quickly restore its capacities thanks to the consistent implementation of clearly planned measures aimed at realizing its internal and external potentials.In conclusion, the author emphasizes the importance of the European vector of food industry development, which will contribute to the development strategy of food industry entities in the context of the macroeconomic environment, the creation and implementation of innovations to strengthen the competitiveness of the food industry, structural transformation and the implementation of international quality standards.
Keywords: food industry; innovative business; technologies; innovative business strategies; innovative development models; development priorities; business model